Taking the Name of the Lord in Vain in Early Modern Italy - Biasiori, Lucio (Church history and religious culture, 2024)
Drawing from a rich array of sources, including trial records, sermons, and literary works, the essay investigates the ambiguities surrounding the definition and punishment of blasphemy in early modern Italy. The essay delves into the jurisdictional tensions between secular and ecclesiastical authorities in prosecuting blasphemers, the social identities of those accused of blasphemy, and the intertwining of blasphemy with other perceived vices, such as sodomy. The author also traces the gradual decriminalization of blasphemy, from its initial perception as a grave sin to its eventual marginalization as a bourgeois vice. Ultimately, the essay invites readers to reflect on the enduring relevance of the blasphemy debate in contemporary societies grappling with the tensions between freedom of expression and respect for religious beliefs.